Factors of migration and job satisfaction level among foreign-educated nurses in Malaysia - Lee, Su Yen (2021)
Global migration and international recruitment have become trends in the nursing profession. Nurse migration to Malaysia was once a common phenomenon but has declined over the years. However, this number of foreign-educated nurses in Malaysia may be underestimated. Many of them working in clinics, nursing homes, and private homes were not required to register with the Malaysia Nursing Board. Exploring the migration of foreign-educated nurses in Malaysia can provide new insights on their population and factors affecting their migration to the country. This study examines the migration of foreign-educated nurses in Malaysia, including factors affecting migration and their job satisfaction level. A cross-sectional design with purposive and snowball sampling method was conducted on foreign-educated nurses working in Malaysia. Foreign-educated nurses on the list from Malaysian Nursing Board were contacted, the study's purpose explained, and additional information was obtained from nurses who agreed to participate. The respondents then introduced their friends or colleagues who were either registered or unregistered with the board. Thus, snowball sampling began with sharing contact information between individuals. A structured questionnaire originated from Oda et al. (2016) was used to collect data. The questionnaire comprises four sections: respondents’ profile, nursing education, working abroad, and job satisfaction. Subjects (n=102) participated in the study. The majority of the foreign-educated nurses who participated in this study were unregistered with the Malaysian Nursing Board (79.4%), worked as registered nurse (86.3%) in nursing or private homes (75.5%). 68.6% of the foreign-educated nurses were females, Christians (73.5%), from Philippines (67.6%) and obtained a bachelor’s degree certificate (80.4%). Findings revealed more than 50% of the foreign-educated nurses stated that the pull factors affecting their migration to the country were higher salary and benefits, better quality of day-to-day life, self-respect and dignity, low recruitment and processing fees, children’s education and future, and high level of nursing skills and technology in Malaysia. The main push factors causing participants to migrate to Malaysia were low salary and few benefits in their own country (68.6%), high ratio of patients to nursing care (64.7%), poor working conditions (58.8%), problem or corruption in obtaining employment (57.8%) and limited opportunities for promotion and career advancement (56.9%). The demographic status of the foreign-educated nurses was correlated with the pull and push factors (p<0.05). 85.3% of the foreign-educated nurses expressed a positive satisfaction level, primarily when serving the sick and needy (85.3%). The results revealed significant differences in job satisfaction of registered and unregistered foreign-educated nurses (p=0.04), nurses with Hindu, and other religions (p=0.03), nurses from India and the Philippines (p=0.02). The majority of the foreign-educated nurses in Malaysia was not register with the Malaysian Nursing Board. However, the overall satisfaction of these nurses was positive. Pull-push factors identified in this study showed a significant relationship with the sociodemographic status. There was a significant difference between sociodemographic status, factors affecting migration, and job satisfaction among the foreign-educated nurses. Nurse managers and policy makers at both entrance and exit points of the migration process should use these findings to facilitate effective management of the consequential challenges of the migration process.